Increased cortisol awakening response was associated with time to recurrence of major depressive disorder - Hardeveld, Florian; Spijker, Jan; Vreeburg, Sophie A.; Graaf, Ron De; Hendriks, Sanne M.; Licht, Carmilla M.M.; Nolen, Willem A.; Penninx, Brenda W.J.H.; Beekman, Aartjan T.F. (Psychoneuroendocrinology, 2014)
•We examine whether HPA-axis parameters predict recurrence of major depression.•A higher CAR is associated with time to recurrence of major depression.•Risk for recurrence due to a higher CAR is not dependent on stress related factors. Although HPA-axis activity has been studied extensively in relation to depression, there is no consensus whether HPA-axis parameters predicts major depressive disorder (MDD) recurrence. We investigated whether HPA-axis parameters (cortisol awakening response (CAR), the dexamethasone suppression test (DST) and evening cortisol) predict time to recurrence in remitted subjects with a history of MDD and whether childhood trauma and life events interact with HPA-axis parameters in increasing the risk for recurrence. Data were derived from 549 subjects with a lifetime diagnosis of MDD in remission for at least six months preceding the baseline assessment of the Netherlands Study of Depression and Anxiety (NESDA). Subjects were followed up with two interviews over the course of four years to assess recurrence. DSM-IV based diagnostic interviews were used to assess time to recurrence of MDD. Seven salivary cortisol samples collected at baseline with information on CAR, evening cortisol and the DST. Hazard ratios were calculated using Cox regression analysis, adjusted for covariates. A higher CAR was associated with time to recurrence of MDD (HR=1.03, 95%CI 1.003–1.060, p=0.03) whereas evening cortisol and DST were not. No interactions between HPA-axis parameters and stress-related factors were found. Our data support previous studies reporting that subjects with a higher CAR are more vulnerable to recurrence of MDD.